Implementasi Work-Life Balance dalam Meningkatkan Kinerja Karyawan di Kelurahan Putat Gede Kecamatan Sukomanunggal Kota Surabaya - Marhaeningtyas, Suci; Puspita Ningrum, Febyana; Diyanti Cahyarini, Echa; Amaliyah; Dimisqiyani, Erindah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The company’s operational activities cannot run smoothly and well without being supported by qualified human resources. Humans are social creatures where human life does not only interact in the world of work. However, the digital era has changed the order of human life to be fast-paced and complex. This, without realizing it, has an unfavorable effect on the lives of employees. Increasing work demands are the cause of employees having inadequate psychological health. The purpose of this research is to find out the implementation of work-life balance which is expected to support the performance of employees. The research method used is a qualitative method with interview techniques and the use of literature studies as a supporting reference. The results of this study indicate that the implementation of work-life balance in Putat Gede Village is still not optimal. This research recommends policies that better support work-life balance to improve employee performance in the form of the use of technology in community services and policy making that supports the implementation of work-life balance in the workplace, complementing the workplace with facilities to relax employees, providing additional leave to employees, and implementing rest hours during the day in order to maintain employee productivity